Novel nanoinsecticides based on essential oils to control the German cockroach - Werdin Gonzalez, Jorge Omar (2014)
The physicochemical characterization and residual insecticidal activity of poly(ethylene glycol) (PEG) nanoparticles containing essential oils (EOs) from geranium (Geranium sp.) and bergamot (Citrus reticulata L.) were evaluated against Blatella germanica for 1 year. The nanoparticles’ size increased during the storage time from <235 to <450 nm; the EO content decreased approximately 50 %, and the abundance of the major components did not show any differences between pre- and post-formulation. The surface characteristics of nanoparticles were analyzed by transmission electronic microscopy. The EO nanoparticles produced a notable increase in the residual contact toxicity apparently because of the slow and persistent release of the active terpenes. In addition, the nanoformulation enhanced the EO contact toxicity. The results indicate that these novel systems could be developed as control agents against German cockroaches.